Do Patients with Type 2 Diabetes Mellitus Know about Specific Dietary Recommendations? - H, Tohid; WA, Wan Farzihan; A, Saharuddin; AR, Mohd Radzniwan; RJ, Teh; M, Noor Azimah (IIUM Medical Journal Malaysia, 2017)
INTRODUCTION: Diabetic patients generally have a good idea about healthy diet however their awareness regarding specific dietary recommendations is questionable. Thus, this paper aims to examine the awareness regarding specific dietary components among diabetic patients at a primary care clinic and its influence on self-reported dietary practice. MATERIALS AND METHODS: The Summary of Diabetes Self-Care Activities (SDSCA) questionnaire (English-Malay version) was used. It was adapted with additional questions to assess respondents’ awareness on: (1) healthful eating plan, (2) the quantity of one serving of fruits and vegetables, (3) choices and the allowed quantity of high fat food intake, (4) meaning of carbohydrate, and (5) carbohydrate spacing per day. RESULTS: From the 360 respondents, 85.0% knew about healthful eating plan. However, those who were unaware of the meaning of carbohydrate, carbohydrate spacing, the allowed high fat food intake, and the quantity of one serving of fruits and vegetables were 34.1%, 47.5%, 40.0%, and 30.8% respectively. Generally, the dietary practice reported by those who knew ‘one serving of fruits and vegetables’ (p<0.001), ‘allowed quantity of high fat food intake’ (p=0.001), ‘meaning of carbohydrate’ (p<0.001), or ‘carbohydrate spacing’ (p<0.001) was significantly different than those who were unaware of these terms. CONCLUSION: Although most respondents knew about healthful eating plan, majority of them were unaware of the specific dietary components, suggesting superficial dietary knowledge. Unfortunately, poor dietary awareness significantly influenced their self-reported dietary practice which could be considered as inaccurate. Thus, strategies to improve their dietary knowledge is necessary at the primary care setting.